PHYSICOCHEMICAL, PHYTOCHEMICAL, SPECTROSCOPIC (LCMS, AND H1-NMR) ANALYSIS OF EXTRACTS OF PLUMBAGO ZEYLANICA - LV, Rama Devi; KADIYALA, K Ganesh; Audipudi, Amrutha Valli (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study aimed to find the physicochemical, phytochemical analysis, and spectroscopic analysis of solvent extracts of the roots of Plumbago zeylanica. Methods: The Soxhlet apparatus was employed to extract individual solvent extracts from the roots of P. zeylanica. In this study, solvent extracts made from the roots of P. zeylanica are tested for their physicochemical properties, phytochemical make-up, and spectroscopic properties. Spectroscopic investigations were conducted with the Bruker 400 MHz nuclear magnetic resonance (NMR) system, manufactured in Switzerland, as well as liquid chromatography mass spectroscopy (LC-MS), a mass spectrometer. Results: The physicochemical study of P. zeylanica roots revealed a moisture content of 10.51%, a total ash content of 2.06%, and an alcohol-soluble extract of 1.72%. In addition, many physical parameters such as color, taste, aroma, and nature were examined. The phytochemical analysis of P. zeylanica revealed the detection of significant phytonutrients, including tannins, carbohydrates, proteins, flavonoids, alkaloids, and sterols, in the root sample. The presence of tannins, carbohydrates, proteins, flavonoids, alkaloids, and sterols in extracts of P. zeylanica was established through spectroscopic analysis using H1-NMR and LCMS. Conclusion: The examination of solvent extracts obtained from the roots of P. zeylanica involved physicochemical, phytochemical, and spectroscopic techniques. This research revealed the presence of many biologically active metabolites, including alkaloids, amino acids, flavonoids, phenols, tannins, and terpenoids. The identification of these metabolites presents a promising prospect for substituting conventional chemical methods in the management of clinically pathogenic and phytopathogenic microorganisms.